Web-gis development for geospatial data dissemination in eu operational programmes - Konstantinos EVANGELIDIS; nastasios AGRIANIDIS; Konstantinos PERAKIS; Theofilos PAPADOPOULOS; Konstantinos PAPATHEODOROU (European Journal of Geography)
The ever increasing penetration of maps - the past decades in the classic web and today in any ‘connected’ smart device - and any type of potentially associated with them information, provides high capabilities of disseminating the outputs and results of a project especiallywhen these are possessing spatial identity. This, combined with the increasingly strict dissemination requirements set by European Union for the beneficiaries of its funded Operational Programmes generates reasonable challenges to explore the capabilities of Web- GIS technologies for geospatial data dissemination purposes. Towards this direction, this paper attempts a review of the EU legislative framework established on top of INSPIRE directive and dealing with geospatial data and services critical issues such as: Metadata, Harmonization, Interoperability and Invocability. Through the experiences gained by the participation of authors in a Black Sea Basin Joint Operational Programme, a Web-GIS end user interface is presented along with the particularities and special requirements identified during project implementation. Furthermore, a demonstration of geospatial services invocability fulfilment is provided along with technical solutions.